Effect of Bay Leaf Extract (Syzygium polyanthum) on Renal Histopathology in Ibuprofen-Induced White Rats (Rattus norvegicus) - Angel Tiurma Butar; Efrisca M. Br. Damanik; Regina M. Hutasoit; Muhajirin Dean (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Excessive use of nonsteroidal anti-inflammatory drugs (NSAIDs), especially ibuprofen, can cause Acute Kidney Injury (AKI) through oxidative stress and prostaglandin inhibition. Syzygium polyanthum leaves contain bioactive compounds such as flavonoids and tannins, which have antioxidant and antiinflammatory properties that may protect the kidneys. This study aimed to evaluate the nephroprotective effect and determine the optimal dose of ethanol extract of Syzygium polyanthum leaves on ibuprofeninduced renal damage in rats. Thirty-six male Sprague Dawley rats were divided into six groups: Negative Control (K-), Acute Positive Control (K+A), Recovery Positive Control (K+B), and three treatment groups (P1, P2, P3). Kidney damage was assessed using the EGTI scoring system (Endothelial, Glomerular, Tubular, Interstitial). Data were analyzed with the Kruskal-Wallis test followed by Dunn’s Post Hoc test. The analysis revealed significant differences in renal damage scores among the groups. The acute positive control group exhibited the highest level of renal injury. Among the treatment groups, the 150 mg/kgBW dose (P2) demonstrated the most optimal improvement, even exceeding spontaneous recovery. At the highest dose (P3), the protective effect did not increase and instead showed a tendency toward reduced efficacy, reflecting a hormetic phenomenon. The ethanol extract of Syzygium polyanthum leaves exerts significant nephroprotective effects against ibuprofen-induced histopathological damage to the renal epithelium, tubules, glomeruli, and interstitial tissue, with an optimal dose of 150 mg/kgBW.